Determination of 16 EPA PAHs in food using gas and liquid chromatography - Agus, Baizura Aya Putri; Rajentran, Komati; Selamat, Jinap; Shanti Dwita Lestari; Umar, Nasiru Bilkisu; Hussain, Norhayati (Elsevier, 2023)
Polycyclic aromatic hydrocarbons (PAHs) in food are discussed in terms of their occurrence, legal limits, sample preparation, identification, and quantification. Recent approaches for optimizing the polycyclic aromatic hydrocarbons (PAHs) extraction from food or food-related products and the subsequent clean-up processes during sample preparation are highlighted in relation to the study's specific objectives. Basic information regarding the performances of analytical procedures for PAH quantification is also summarized. Gas chromatography (GC) and high-performance liquid chromatography (HPLC) coupled with mass spectrometry (MS), flame ionization detectors (FID), ultraviolet detectors (UV), and fluorescent detectors (FLD) are among the most widely used techniques for identifying and quantifying PAHs in food. The validation of the method’s performance such as linearity, the limit of detection (LOD), limit of quantification (LOQ), precision (repeatability, intermediate precision, and reproducibility), HORRAT values (Horratr and HorratR), accuracy (recovery) and measurement uncertainty are also briefly discussed.